Industrial Engineering in the Big Data Era Selected Papers from the Global Joint Conference on Industrial Engineering and Its Application Areas, GJCIE 2018, June 21-22, 2018, Nevsehir, Turkey - Calisir, Fethi; Cevikcan, Emre; Camgoz Akdag, Hatice (Lecture Notes in Management and Industrial Engineering, 2019)
This book gathers extended versions of the best papers presented at the Global Joint Conference on Industrial Engineering and Its Application Areas (GJCIE), held in Nevsehir, Turkey, on June 21-22, 2018. They reports on industrial engineering methods and applications, with a special focus on the advantages and challenges posed by Big data in this field. The book covers a wide range of topics, including decision making, optimization, supply chain management and quality control.